2019
DOI: 10.1002/cmdc.201900193
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Validation of DegS As a Target for the Development of Antibiotics with a Novel Mode of Action

Abstract: Despite the availability of hundreds of antibiotic drugs, infectious diseases continue to remain one of the most notorious health issues. In addition, the disparity between the spread of multidrug‐resistant pathogens and the development of novel classes of antibiotics exemplify an important unmet medical need that can only be addressed by identifying novel targets. Herein we demonstrate, by the development of the first in vivo active DegS inhibitors based on a pyrazolo[1,5‐a]‐1,3,5‐triazine scaffold, that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In this case, the amination/cyclization process is promoted by the couple HgCl 2 /TFA and DMF as solvent. Chu et al and Kaiser et al further reported a multistep synthesis of pyrazolo­[1,5- a ]­[1,3,5]­triazine-2,4-diamine derivatives as potent protein kinase CK2 inhibitors and antibiotics (Scheme , c) . Although the above contributions we discuss here are useful for the construction of pyrazolo­[1,5- a ]­[1,3,5]­triazines, , these reactions proceed under the conditions of high reaction temperature, microwave irradiation, and multistep reactions.…”
Section: Introductionmentioning
confidence: 93%
“…In this case, the amination/cyclization process is promoted by the couple HgCl 2 /TFA and DMF as solvent. Chu et al and Kaiser et al further reported a multistep synthesis of pyrazolo­[1,5- a ]­[1,3,5]­triazine-2,4-diamine derivatives as potent protein kinase CK2 inhibitors and antibiotics (Scheme , c) . Although the above contributions we discuss here are useful for the construction of pyrazolo­[1,5- a ]­[1,3,5]­triazines, , these reactions proceed under the conditions of high reaction temperature, microwave irradiation, and multistep reactions.…”
Section: Introductionmentioning
confidence: 93%
“…7 A). Bongard et al reported that modified pyrazolo[1,5- a ]-1,3,5-triazines were potential E. coli DegS inhibitors [19] . They demonstrated these compounds could repress the outer membrane stress response and act synergistically with antibiotics in E. coli ( Fig.…”
Section: Drug Development Targeting Htra Proteinsmentioning
confidence: 99%
“…Certain HtrA proteins can be secreted from the cell to facilitate bacterial invasion [18] . Their significant physiological functions, particularly those in virulence and antibiotic resistance, suggests that members of the HtrA family constitute attractive drug targets [10] , [19] , [20] , [21] , [22] .…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazolo [1,5-a] [1,3,5]triazine is a heterocyclic system which has generated considerable interest in the communities of academic and industrial medicinal chemists [1,2]. This nitrogen-rich heterocyclic core was intensively developed as a bioisosteric substitute of biogenic purines (e.g., adenine, guanine, and xanthine in Figure 1) for the conception of potentially bioactive compounds in a wide range of biological applications [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In this context, numerous synthetic routes of various substituted pyrazolo [1,5-a] [1,3,5]triazines have been yet reported [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%